Just-In-Time: Review of Empirical Studies - Ribeiro, Patrícia Raquel; Machado, Maria João (International Journal of Business, Economics and Management, 2014)
This study is a review of literature and empirical studies on the subject of Just-in-Time (JIT), conducted by a selection of articles published in international journals included in the ISCTE Business School Ranking, released since the 1980s to the present days. The purpose of this research was to compare the key features and benefits of JIT reported by the theory with the practice reported by companies in empirical studies already conducted. In addition, the percentage of use and the importance of JIT in different countries were also analyzed. A small case study of a Japanese enterprise – Mazda Motor Corporation – was also conducted in order to complement the investigation on the subject. As a result, it became clear that there were companies using JIT philosophy with distinct features and benefits that were not reported in the literature on the subject. The United Kingdom had the highest percentage of JIT use, and in broad terms, JIT was not frequently used in the majority of the countries surveyed. One reason for this can be explained by the fact that companies did not attribute a high degree of importance for JIT practices. This means that the companies analyzed did not implement JIT practices extensively.